Conjunctival rhinosporidiosis mimicking pyogenic granuloma—A case report - S Sreevibya; S Manavalan; M Nithya; B Krishnaswamy; K Sathish (TNOA Journal of Ophthalmic Science and Research, 2023)
Rhinosporidiosis is a chronic granulomatous infection caused by Rhinosporidium seeberi endemic in India, commonly in Tamil Nadu, Karnataka, Pondicherry, Chhattisgarh, etc. Ocular rhinosporidiosis though uncommon can affect the conjunctiva, lacrimal sac, sclera, and eyelids. In the conjunctiva, the palpebral conjunctiva is affected the most. Here, we discuss a case of a 14-year-old male who presented with a polypoidal mass in the bulbar conjunctiva mimicking a pyogenic granuloma, which on excision biopsy was confirmed as rhinosporidiosis. Diagnosis is based mainly on strong clinical suspicion and can be confirmed on excision biopsy.